Representação e recuperação da informação em campanhas de publicidade no Facebook ADS: estratégias e proposição de protocolos de descrição - Miguel, Daniele Teixeira (Universidade Federal de São Carlos, 2023)
This research investigates the representation and retrieval of information, specifically focusing on the construction of nomenclature for Facebook Ads media campaigns. The overall objective is to define protocols for describing media campaigns on Facebook Ads, with the aim of expanding reach in information retrieval mechanisms. This is an applied research that adopts a qualitative approach and exploratory objectives. The employed methodology includes bibliographic and documentary research, providing a robust and in-depth analysis of the topic. The study critically analyzes the lack of standardization in the definition of nomenclature for ads broadcasted on the Facebook Ads platform and how this interferes with efficient information retrieval. As a result, the research presents a concrete proposal for standardizing nomenclature, based on the concept of folksonomy. This proposal is specifically directed towards the areas of campaigns, ad groups, and ads within the Facebook Ads platform, offering a practical and effective solution to improve information retrieval in these areas.
Information representation and retrieval in Facebook ADS advertising campaigns: strategies and proposed description protocols
Keywords: Marketing digital; Facebook ADS; Representação da informação; Recuperação da informação; Ciência da Informação; Digital marketing; Information representation; Information retrieval; Information Science; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::COMUNICACAO VISUAL; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::TEORIA DA COMUNICACAO